Estudo de caso da construção da Comunidade que Sustenta a Agricultura (CSA) Guajuvira, no município de São José dos Campos, Vale do Paraíba-SP - Zerlote, Matheus Reis (Universidade Federal de São Carlos, 2024)
Profound changes began to take place in the agrarian structure from the 1950s onwards, which began the so-called "Green Revolution” which sought to enhance agricultural productivity with the use of chemical increments and technological machinery. In order to counter this form of production and commercialization, The Community that Sustains Agriculture (CSA) was born, which values the production of organic and/or agroecological foods combined with subsidizing production by consumers in urban areas. This case study described the formation of CSA Guajuvira in the municipality of São José dos Campos, in the Vale do Paraíba macroregion in the state of São Paulo. The case study methodology was used in order to collect data in ways: participatory, oral history and obtaining primary and secondary data through interviews, thus, systematizing information to understand the limitations, potential and challenges that this marketing model presents for farmers and co-farmers. As main results, information was obtained regarding the historical, social and environmental formation of CSA Guajuvira, as well as the perspective of CSA co-farmers regarding their participation in the community and possible changes in its structure.
Case study of the construction of the Community that Supports Agriculture (CSA) Guajuvira, in the municipality of São José dos Campos, Vale do Paraíba-SP
Keywords: Agroecologia; Rural-urbanização; Circuito-curto-de-comercialização; Economia associativa; Agroecology; Rural-urbanization; Short marketing circuit; Associative economy; CIENCIAS AGRARIAS